Ultralow-temperature sintered ceramic material as well as preparation method and application thereof
By mixing H3BO3 with ceramic raw materials and sintering under uniaxial pressure, the problem of excessive sintering temperature of ceramic materials is solved, and the densification of ceramic materials below 100℃ is achieved. It is suitable for silicon-based chip packaging and has excellent dielectric and thermal conductivity.
Patent Information
- Application Number
- CN202411023941.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2024-12-17
AI Technical Summary
The sintering temperature of existing ceramic materials is too high, which limits its application in silicon-based chip packaging, especially densification below 100°C is difficult to achieve.
Using H3BO3 as a sintering additive, mix with ceramic raw materials such as Al2O3, AlN, SiC, and form composite powder by ball milling and grinding. The ultra-low temperature sintering of ceramic materials is achieved by using two pressure-holding times below 100°C, and the layered molecular structure of H3BO3 is used. The hydrogen bond is densified under uniaxial pressure.
The densification of ceramic materials was successfully achieved at 25 to 100°C, forming a composite ceramic material with good quality factor, suitable dielectric constant and excellent thermal conductivity, suitable for silicon-based chip packaging and other electronic devices.
Smart Images

Figure CN119143512A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of low-temperature sintered ceramic materials, and in particular to an ultra-low-temperature sintered ceramic material and a preparation method and application thereof. Background Art
[0002] The integrated circuit industry is the cornerstone supporting the development of the modern information society and the core component of electronic devices. Miniaturization, integration, high energy efficiency and high reliability are the development trends of integrated circuits and electronic devices. Packaging metals, polymers, silicon-based and ceramic materials together is an important process in integrated circuit packaging. However, conventional ceramic materials usually require sintering densification at temperatures above 1000°C, while the tolerance temperature of silicon-based chips is 425°C. Exceeding this temperature will cause ion diffusion of silicon-based chips and damage electronic components. Usually, in order to reduce the sintering temperature of ceramics, sintering aids are added to ceramics, such as low temperature co-fired ceramics (LTCC) technology, which adds glass phases and low melting point oxides, etc., to produce a liquid phase at a lower temperature to promote the mass transfer process, thereby reducing the densification temperature of the ceramics. The sintering densification temperature is between 850°C and 950°C. In recent years, ultra low temperature co-fired ceramic (ULTCC) materials have gradually emerged. By developing material systems with low intrinsic sintering temperatures, the sintering densification temperature of ceramics can be reduced to below 700°C. The ceramic system with the lowest sintering temperature in the existing ULTCC technology is K 2 Mo 2 O 7 , its sintering temperature is 460℃, which is still higher than the tolerance temperature of silicon-based chips, thus limiting the application of ceramic materials in integrated circuit packaging, such as silicon-based chip packaging. How to achieve densification of ceramic materials within 100℃ is an urgent problem that needs to be solved.
[0003] Therefore, the existing technology still needs to be improved and developed. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, an embodiment of the present invention provides an ultra-low temperature sintered ceramic material and a preparation method and application thereof, aiming to solve the problem in the prior art that the ceramic sintering temperature is too high, resulting in its limited application in silicon-based chip packaging.
[0005] The first aspect of the present application is to provide a method for preparing an ultra-low temperature sintered ceramic material, comprising the following steps:
[0006] Preparation of composite powder: placing a matrix formed by mixing ceramic raw materials and sintering aids in a ball mill, adding ball milling beads and ball milling media, mixing, ball milling, and then drying to form the composite powder;
[0007] Preparing the pre-sintered material: sieving the composite powder, adding deionized water, and grinding in a mortar to form the pre-sintered material;
[0008] Preparation of ultra-low temperature sintered ceramic material: adding the pre-sintered material into a mold, and performing ultra-low temperature sintering below 100° C. to form the ultra-low temperature sintered ceramic material. The ultra-low temperature sintering process includes two pressure holdings, and the first pressure holding discharges air to improve the densification effect of the second pressure holding.
[0009] Preferably, the ceramic raw material is Al 2 O 3 , AlN, SiC; the sintering aid is H 3 BO 3 Powder; by weight, the ceramic raw material is 1 to 50 parts, the H 3 BO 3 The powder is 1 to 50 parts.
[0010] Preferably, the ceramic raw material is in the form of flake particles with a diameter of 3 to 10 μm and a thickness of 0.1 to 1 μm.
[0011] Preferably, the ball milling beads are zirconium balls, the composition of which is ZrO 2 ; The ball milling medium is at least one of acetone, butanone, and hexanone.
[0012] Preferably, the mass ratio of the matrix, the ball milling beads and the ball milling medium is 1:(2-4):1.
[0013] Preferably, the ball milling is controlled at a speed of 300 to 500 rpm for 4 to 8 hours; the drying is controlled in a blast drying oven at a temperature of 40 to 80° C. for 12 to 36 hours.
[0014] Specifically, the process of sieving the composite powder, adding deionized water, grinding the composite powder in a mortar, and forming the pre-sintered material comprises the following steps:
[0015] Sieve the composite powder through a sieve, wherein the mesh number of the sieve is 60 to 200 meshes;
[0016] Deionized water is added to the composite powder, and the composite powder is ground in the mortar so that the deionized water wets the tiny particles of the composite powder.
[0017] Specifically, the pre-sintered material is added into a mold and subjected to ultra-low temperature sintering below 100° C. to form the ultra-low temperature sintered ceramic material. The ultra-low temperature sintering process includes two pressure holding steps:
[0018] The pre-sintered material is placed in a mold, and the first pressure holding is performed to expel air, the pressure is set to 100-200 MPa, the sintering temperature is 25-100° C., and the pressure holding time is 20-40 min;
[0019] Then, a second holding pressure is performed to sinter the pre-sintered material, the pressure is set to 100-800 MPa, the sintering temperature is 25-100° C., and the holding time is 40-150 min;
[0020] Then, the mixture is dried at 65° C. to form the ultra-low temperature sintered ceramic material.
[0021] The second aspect of the present application is to provide an ultra-low temperature sintered ceramic material, which is prepared by the above-mentioned method for preparing an ultra-low temperature sintered ceramic material.
[0022] A third aspect of the present application is to provide an application of an ultra-low temperature sintered ceramic material, wherein the ultra-low temperature sintered ceramic material is applied to the packaging of silicon-based chips.
[0023] Compared with the prior art, the present application mainly has the following beneficial effects: the preparation method of the ultra-low temperature sintered ceramic material of the present application includes: preparing composite powder: placing a matrix formed by mixing ceramic raw materials and sintering aids in a ball mill, adding ball milling beads and ball milling media, mixing and ball milling, and then drying to form the composite powder; preparing pre-sintered material: adding deionized water to the composite powder after sieving, grinding in a mortar to form the pre-sintered material; preparing ultra-low temperature sintered ceramic material: adding the pre-sintered material to a mold for ultra-low temperature sintering below 100°C to form the ultra-low temperature sintered ceramic material, and the ultra-low temperature sintering process includes two pressure holdings. The raw materials of the present application are easy to obtain, the process is simple, and by placing H 3 BO 3 As a sintering aid, H 3 BO 3 The deformable property under uniaxial pressure allows the ceramic material to be densified under ultra-low temperature conditions of 25 to 100°C by applying pressure, forming a composite ceramic material with good quality factor, suitable dielectric constant, and excellent thermal conductivity. It can also be co-fired with silicon-based chips and can be used in semiconductor packaging, LTCC devices or ULTCC devices, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 The present invention is a flow chart of a method for preparing an ultra-low temperature sintered ceramic material according to an embodiment of the present application.
[0026] Figure 2 Al of Example 1 of the present application 2 O 3 -H 3 BO 3 X-ray diffraction spectrum of composite ceramic materials.
[0027] Figure 3 Al of Example 1 of the present application 2 O 3 -H 3 BO 3 Raman spectra of composite ceramic materials.
[0028] Figure 4 Al of Example 1 of the present application 2 O 3 -H 3 BO 3 Microscopic image of the bonding interface between composite ceramic material and silicon-based chip after packaging. DETAILED DESCRIPTION
[0029] The following will be combined with the implementation methods of this application to clearly and completely describe the technical solutions in the implementation methods of this application. Obviously, the described implementation methods are only part of the implementation methods of this application, not all of the implementation methods. Based on the implementation methods in this application, all other implementation methods obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0030] It should be understood that the terms used in this specification of the embodiments of the present application are only for the purpose of describing specific embodiments and are not intended to limit the embodiments of the present application. As used in the specification of the embodiments of the present application and the appended claims, unless the context clearly indicates otherwise, the singular forms of "a", "an" and "the" are intended to include plural forms.
[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0032] The first aspect of the present application is to provide a method for preparing an ultra-low temperature sintered ceramic material. Figure 1 As shown, the following steps are included:
[0033] S10, preparing composite powder: placing a matrix formed by mixing ceramic raw materials and sintering aids in a ball mill, adding ball milling beads and ball milling media, mixing and ball milling, and then drying to form the composite powder;
[0034] S20, preparing a pre-sintered material: sieving the composite powder, adding deionized water, and grinding the composite powder in a mortar to form the pre-sintered material;
[0035] S30, preparing ultra-low temperature sintered ceramic material: adding the pre-sintered material into a mold, and performing ultra-low temperature sintering below 100° C. to form the ultra-low temperature sintered ceramic material, wherein the ultra-low temperature sintering process includes two pressure holdings, wherein the first pressure holding discharges air to improve the densification effect of the second pressure holding.
[0036] Specifically, the ceramic raw material is Al 2 O 3 , AlN, SiC, the sintering aid is H 3 BO 3 Powder; by weight, the ceramic raw material is 1 to 50 parts, the H 3 BO 3 1 to 50 parts. These ceramic materials and H 3 BO 3 Crystalline powders are easily available and the material cost is low.
[0037] Specifically, Al 2 O 3 , AlN, and SiC are common ceramic materials that can only be densified by sintering at high temperatures above 1000°C. 3 BO 3 The powder is compounded with the above ceramic materials to achieve ultra-low temperature sintering of the composite ceramic materials below 100°C. 3 BO 3 It is a layered molecular crystal, with H 3 BO 3 The molecules are bonded together by hydrogen bonds, and the layers are bonded together by van der Waals forces. 3 BO 3The weak bonds in the ceramic make it easy for the particles to rearrange and reshape under mechanical force and water, so that densification can be easily achieved through plastic deformation under uniaxial pressure. 3 BO 3 Mix with deionized water and grind thoroughly to make the molecules contact with each other as much as possible at the microscopic level, and then sinter under pressure and low temperature to achieve ceramic and H 3 BO 3 Densification of composite ceramic materials.
[0038] Specifically, the ceramic raw material is a flaky particle with a diameter of 3 to 10 μm and a thickness of 0.1 to 1 μm. Preferably, the ceramic raw material is a flaky high thermal conductivity ceramic particle with a particle diameter of 5 to 7 μm and a thickness of 0.6 to 1 μm.
[0039] Specifically, the ball milling beads are zirconium balls, and the composition is ZrO 2 Zirconium balls are used as ball milling beads. They have high hardness and provide energy for the ball milling process, which makes the ceramic particles and H 3 BO 3 The mixed powder of particles is evenly dispersed, and the zirconium balls have stable chemical properties and will not chemically react with ceramic materials and ball milling media, thereby ensuring the stability of the performance of the ceramic materials.
[0040] Specifically, the ball milling medium is at least one of acetone, butanone and hexanone. Preferably, the ball milling medium is acetone. The ball milling medium is liquid, and the addition of the ball milling medium helps to evenly disperse the mixed powder.
[0041] Specifically, the mass ratio of the matrix, the ball milling beads, and the ball milling medium is 1: (2-4): 1. Under this ratio, the matrix and the ball milling medium have the same mass, both less than the ball milling beads, which is conducive to the matrix (ceramic particles and H) in the ball milling process. 3 BO 3 Uniform dispersion of mixed powder of particles.
[0042] Specifically, in step S10, the ball milling is controlled under the following conditions: a rotation speed of 300 to 500 rpm and a time of 4 to 8 hours.
[0043] Specifically, in step S10, the drying control conditions are: drying in a blower box, and setting the temperature to 40-80° C. and the time to 12-36 hours.
[0044] Specifically, step S20, preparing a pre-sintered material: sieving the composite powder, adding it to deionized water, and grinding it in a mortar to form the pre-sintered material, comprises the following steps:
[0045] S21, sieving the composite powder through a sieve, wherein the mesh number of the sieve is 60 to 200 meshes;
[0046] S22, adding deionized water to the composite powder, and grinding the composite powder in the mortar so that the deionized water wets the tiny particles of the composite powder.
[0047] Specifically, in step S21, the ball milling beads and the composite powder with larger particles are screened out with a screen, so that the retained composite powder is more uniform and fine, and the dispersion effect is better, which is helpful for the subsequent ultra-low temperature sintering. 3 BO 3 Preferably, the mesh size of the sieve is 80 to 120 meshes.
[0048] Specifically, in step S21, deionized water is added to the composite powder, and the composite powder is ground in the mortar so that the deionized water wets the micro particles of the composite powder. The grinding process will fully wet the composite powder, that is, the ceramic particles and H 3 BO 3 Particles, which helps the ceramic densification in the subsequent ultra-low temperature sintering process. Specifically, by weight, the composite powder is 80 to 99 parts, and the deionized water is 1 to 20 parts. Preferably, the mass ratio of the composite powder to the deionized water is 10:1.
[0049] Specifically, the mixture was left to stand for 20 to 24 hours after grinding to allow the deionized water to better wet the ceramic particles and H 3 BO 3 Particles.
[0050] Specifically, step S30, adding the pre-sintered material into a mold, and further, ultra-low temperature sintering below 100° C. to form the ultra-low temperature sintered ceramic material, wherein the ultra-low temperature sintering process includes two pressure holdings, and includes the following steps:
[0051] S31, placing the pre-sintered material in a mold, performing the first pressure holding to expel air, setting the pressure to 100-200 MPa, the sintering temperature to 25-100° C., and the pressure holding time to 20-40 min;
[0052] S32, then performing a second pressure holding process to sinter and densify the pre-sintered material, setting the pressure to 100-800 MPa, the sintering temperature to 25-100° C., and the pressure holding time to 40-150 min;
[0053] S33, then drying at 65°C to form the ultra-low temperature sintered ceramic material.
[0054] Specifically, the ultra-low temperature sintering process includes two pressure holdings. Air will enter the process of pouring the pre-sintered material into the mold. The first pressure holding is to expel the air to prevent the air from affecting the ultra-low temperature sintering effect and being detrimental to the densification of the ceramic material. The pressure during the first pressure holding is 100-200MPa, the sintering temperature is 25-100°C, and the pressure holding time is 20-40min. In one embodiment, the pressure of the first pressure holding is 100MPa, the sintering temperature is 40°C, and the pressure holding time is 40min.
[0055] Preferably, the pressure of the second pressure holding is higher than the pressure of the first pressure holding. Preferably, the sintering temperature is 25-60°C.
[0056] Specifically, the second pressure holding after the first pressure holding is the most critical process of ultra-low temperature sintering. 3 BO 3 It is a layered molecular crystal, with H 3 BO 3 The molecules are bonded by hydrogen bonds, and the layers are bonded by van der Waals forces. During the second pressure holding, deionized water is used as the transient liquid phase and uniaxial pressure is applied so that H 3 BO 3 The particles are rearranged and reshaped under the action of uniaxial pressure and water, so that densification can be easily achieved through plastic deformation under uniaxial pressure. In the previous step, the flaky ceramic particles are made of H by ball milling and grinding. 3 BO 3 The particles are well dispersed, so H 3 BO 3 The plastic deformation of the molecules will assist in the dispersion of H 3 BO 3 The flaky ceramic particles are densified to form a densified composite ceramic material, thereby realizing the preparation of ultra-low temperature sintered ceramic materials.
[0057] Specifically, the pressure during the second pressure holding is 100-800 MPa, the sintering temperature is 25-100° C., and the pressure holding time is 40-150 min.
[0058] In one embodiment, the second pressure holding process is performed at a pressure of 500 MPa, a sintering temperature of 50° C., and a pressure holding time of 120 min.
[0059] In step S33, the composite ceramic material formed by ultra-low temperature sintering is placed in a blast oven at 65°C and dried for 12 to 36 hours to dry the moisture, thereby forming an ultra-low temperature sintered ceramic material with excellent performance, the composition of which is Al 2 O 3 -H 3 BO 3 、AlN-H 3 BO 3、SiC-H 3 BO 3 At least one of .
[0060] During the whole process of ball milling, drying, screening, grinding, sintering and drying, the ceramic particles (Al 2 O 3 , AlN, SiC), H 3 BO 3 There is no chemical reaction between the substances such as zirconium balls and acetone. Only during the ultra-low temperature sintering process, H 3 BO 3 Particles and Al 2 O 3 , AlN and SiC flaky particles are densified together.
[0061] The second aspect of the present application is to provide an ultra-low temperature sintered ceramic material, which is prepared by the above-mentioned method for preparing an ultra-low temperature sintered ceramic material.
[0062] Specifically, the composition of the ultra-low temperature sintered ceramic material is Al 2 O 3 -H 3 BO 3 、AlN-H 3 BO 3 、SiC-H 3 BO 3 At least one of .
[0063] Specifically, the thermal conductivity of the ultra-low temperature sintered ceramic material is above 6 W / (m·K), the dielectric constant is 3.3 to 7.2, and the dielectric loss is (1 to 9)×10 -4 , with the characteristics of low dielectric constant, low dielectric loss and high thermal conductivity.
[0064] A third aspect of the present application is to provide an application of an ultra-low temperature sintered ceramic material, wherein the ultra-low temperature sintered ceramic material is applied to the packaging of silicon-based chips.
[0065] Specifically, the process of preparing the composite powder and the pre-sintering material in the packaging process is consistent with the above, and will not be repeated here. The ultra-low temperature sintering packaging process of the silicon-based chip is described below:
[0066] S40, adding the pre-sintered material and the silicon-based chip into a mold for ultra-low temperature sintering to form a silicon-based chip coated with a low-temperature sintered composite ceramic material, wherein the ultra-low temperature sintering process includes two pressure holdings.
[0067] Specifically include:
[0068] S41, placing the silicon-based chip in the mold, adding the pre-sintered material, and making the silicon-based chip covered by the pre-sintered material;
[0069] S42, implement the first pressure holding to expel air, set the pressure to 100-200 MPa, the sintering temperature to 25-100° C., and the pressure holding time to 20-40 min;
[0070] S43, then performing a second pressure holding process to sinter the pre-sintered material into a shape, setting the pressure to 100-800 MPa, the sintering temperature to 25-100° C., and the pressure holding time to 40-150 min;
[0071] S44, then drying at 65° C. to form the silicon-based chip encapsulated by the ultra-low temperature sintered composite ceramic material.
[0072] Since ultra-low temperature sintering is carried out at a temperature below 100°C, which is far lower than the tolerance temperature of silicon-based chips, the silicon-based chips remain intact. By coating the outer layer with ultra-low temperature composite ceramic materials, a packaged silicon-based chip is formed.
[0073] The technical scheme and technical effect of the present application are described below through specific examples and comparative examples. Table 1 is a comparison table of raw material parameters and sintering temperatures of Examples 1 to 4 and Comparative Examples 1 to 2.
[0074] Table 1 Comparison of raw material parameters and sintering temperatures of Examples 1 to 4 and Comparative Examples 1 to 2
[0075]
[0076] Example 1
[0077] Preparation of Al 2 O 3 -H 3 BO 3 Ultra-low temperature sintered composite ceramic materials, raw material parameters are shown in Table 1:
[0078] (1) Take Al flakes 2 O 3 Powder 20g and H 3 BO 3 20g of powder was mixed and placed in a ball mill, and 80g of zirconium balls and 40g of acetone liquid were added. The speed of the ball mill was set to 300rpm, and the ball mill was milled for 4h. Then the composite powder after ball milling was taken out and placed in a dryer and dried at 65℃ for 12h.
[0079] (2) sieving the dried composite powder to a 100-mesh sieve to remove large particles and zirconium balls. After standing for 20 hours, 100 g of powder smaller than 100 mesh was placed in a mortar, and 10 g of deionized water was added for grinding to form a pre-sintered material.
[0080] (3) The pre-sintered material is placed in a steel mold, subjected to ultra-low temperature sintering, pressure maintained twice, and then dried at 65°C for 12 hours to prepare Al 2 O 3 -H 3 BO 3 Ultra-low temperature sintering of composite ceramic materials, wherein the first pressure holding setting is: pressure of 100MPa, sintering temperature of 25°C, and pressure holding time of 20min; the second pressure holding setting is: pressure of 400MPa, sintering temperature of 25°C, and pressure holding time of 40min.
[0081] Example 2
[0082] Preparation of AlN-H 3 BO 3 Ultra-low temperature sintered composite ceramic materials, raw material parameters are shown in Table 1:
[0083] (1) Take 30 g of flaky AlN powder and H 3 BO 3 30g of the powder was mixed and placed in a ball mill, and 120g of zirconium balls and 60g of acetone liquid were added. The speed of the ball mill was set to 500rpm, and the ball mill was milled for 8h. Then the composite powder after ball milling was taken out and placed in a dryer and dried at 65℃ for 36h.
[0084] (2) The dried composite powder was sieved with a mesh size of 60 to remove large particles and zirconium balls. After standing for 24 hours, 60 g of powder smaller than 60 mesh was placed in a mortar, and 6 g of deionized water was added for grinding to form a pre-sintered material;
[0085] (3) The pre-sintered material is placed in a steel mold, subjected to ultra-low temperature sintering, subjected to two pressure holdings, and then dried at 65°C for 24 hours to prepare AlN-H 3 BO 3 Ultra-low temperature sintering of composite ceramic materials, wherein the first pressure holding setting is: pressure of 200MPa, sintering temperature of 100℃, and pressure holding time of 40min; the second pressure holding setting is: pressure of 300MPa, sintering temperature of 100℃, and pressure holding time of 80min.
[0086] Example 3
[0087] Preparation of SiC-H 3 BO 3 Ultra-low temperature sintered composite ceramic materials, raw material parameters are shown in Table 1:
[0088] (1) Take 50 g of flaky SiC powder and H 3 BO 3 50g of the powder was mixed and placed in a ball mill, and 400g of zirconium balls and 100g of acetone liquid were added. The speed of the ball mill was set to 400rpm, and the ball mill was milled for 6h. Then the composite powder after ball milling was taken out and placed in a dryer and dried at 65℃ for 24h.
[0089] (2) sieving the dried composite powder to a 200-mesh screen to remove large particles and zirconium balls. After standing for 24 hours, 200 g of powder with a mesh size smaller than 200 was placed in a mortar, and 20 g of deionized water was added for grinding to form a pre-sintered material.
[0090] (3) The pre-sintered material is placed in a steel mold, subjected to ultra-low temperature sintering, subjected to two pressure holdings, and then dried at 65°C for 24 hours to prepare SiC-H 3 BO 3 Ultra-low temperature sintering of composite ceramic materials, wherein the first pressure holding setting is: pressure of 150MPa, sintering temperature of 80℃, and pressure holding time of 30min; the second pressure holding setting is: pressure of 800MPa, sintering temperature of 80℃, and pressure holding time of 100min.
[0091] Example 4
[0092] Preparation of coated Al 2 O 3 -H 3 BO 3 The raw material parameters of silicon-based chips made of ultra-low temperature sintered composite ceramic materials are shown in Table 1:
[0093] (1) Take Al flakes 2 O 3 Powder 20g and H 3 BO 3 20g of powder was mixed and placed in a ball mill, and 80g of zirconium balls and 40g of acetone liquid were added. The speed of the ball mill was set to 300rpm, and the ball mill was milled for 4h. Then the composite powder after ball milling was taken out and placed in a dryer and dried at 65℃ for 12h.
[0094] (2) sieving the dried composite powder to a 100-mesh sieve to remove large particles and zirconium balls. After standing for 20 hours, 100 g of powder smaller than 100 mesh was placed in a mortar, and 10 g of deionized water was added for grinding to form a pre-sintered material.
[0095] (3) The pre-sintered material is placed in a steel mold, and then the silicon-based chip is placed in it, so that the silicon-based chip is completely covered by the pre-sintered material, and then ultra-low temperature sintering is performed, and pressure is applied twice, and then dried at 65°C for 12 hours to prepare the Al-coated 2 O 3-H 3 BO 3 The silicon-based chip of the ultra-low temperature sintered composite ceramic material, wherein the first pressure holding setting is: pressure of 100MPa, sintering temperature of 25°C, and pressure holding time of 20min; the second pressure holding setting is: pressure of 400MPa, sintering temperature of 25°C, and pressure holding time of 40min.
[0096] Comparative Example 1 Referring to the Chinese invention patent (application number 201710112874.X) tungsten-based ultra-low temperature co-fired microwave dielectric ceramic material and its preparation method, Na 2 CO 3 or K 2 CO 3 with Bi 2 O 3 and WO 3 As raw material, according to the chemical formula M 0.5 Bi 0.5 WO 4 The ingredients are weighed and prepared according to the molar ratio of , wherein M is one of Na or K, by ball milling, drying, sieving and sintering. The sintering temperature is 580-630° C., which is much higher than the sintering temperature of the present application.
[0097] Comparative Example 2 refers to a Chinese invention patent (application number 202211288841.8) on a low-temperature sintered ceramic material and its preparation method and application, using Na 2 CO 3 、Bi 2 O 3 , WO 3 The low-temperature sintered ceramic material can be sintered at 625°C to 800°C, which is much higher than the sintering temperature of the present application.
[0098] Compared with Comparative Examples 1-2, the raw materials and preparation process of Examples 1-4 of the present application can successfully prepare low-temperature sintered composite ceramic materials at a sintering temperature of 25-100° C. The sintering temperature of the present application is much lower than that of Comparative Examples 1-2.
[0099] Performance Analysis:
[0100] By performing X-ray diffraction tests and Raman tests on the prepared ultra-low temperature composite ceramic materials, X-ray diffraction spectra and Raman spectra are obtained, thereby analyzing whether chemical reactions occur in the materials and whether the ultra-low temperature composite ceramic materials are successfully prepared.
[0101] like Figure 2 As shown, it is Al of Example 1 2 O 3 -H 3 BO 3X-ray diffraction spectrum of composite ceramic materials. This figure can illustrate the H 3 BO 3 and Al 2 O 3 No phase change occurred.
[0102] like Figure 3 As shown, it is Al of Example 1 2 O 3 -H 3 BO 3 Raman spectrum of composite ceramic materials. The peak numbers in the figure represent the intensity of Raman scattering. This figure shows that H 3 BO 3 and Al 2 O 3 There is no bonding between them, indicating that there is no chemical reaction between them.
[0103] like Figure 4 As shown, the Al prepared in Example 4 2 O 3 -H 3 BO 3 Microscopic image of the bonding interface between composite ceramic material and silicon-based chip after packaging. Figure 4 In the figure, the left side is an ultra-low temperature sintered composite ceramic material, and the right side is a silicon-based chip. The boundary structure between the ultra-low temperature sintered composite ceramic material and the silicon-based chip is clear, indicating that the ultra-low temperature sintered composite ceramic material prepared in this application has good compatibility with silicon-based, will not destroy the structure of the silicon-based chip, and can be effectively used for the packaging of silicon-based chips.
[0104] The density was measured by the Archimedean drainage method, the thermal conductivity was measured by the laser flash method, and the dielectric constant and dielectric loss were measured by the resonant cavity method. Table 2 shows the test results of the ultra-low temperature sintered composite ceramic materials of Examples 1 to 3.
[0105] Table 2 Performance analysis of Examples 1 to 3 and Comparative Examples 1 to 2
[0106] serial number density Thermal conductivity Dielectric constant Dielectric loss Example 1 2.6519 5.93 5.34 <![CDATA[7.12×10 -4 ]]> Example 2 2.3038 7.31 5.56 <![CDATA[8.32×10 -4 ]]> Example 3 2.2795 8.44 5.46 <![CDATA[7.97×10 -4 ]]> Comparative Example 1 / / 31.5~37.2 / Comparative Example 2 / / 13~15 /
[0107] As can be seen from Table 2, the ultra-low temperature sintered ceramic material prepared by the technical solution of the present application has the characteristics of low dielectric constant, low dielectric loss and high thermal conductivity, and is an ultra-low temperature sintered material with superior performance. Moreover, the ultra-low temperature sintered composite ceramic materials of Examples 1 to 3 of the present application have an even lower dielectric constant.
[0108] In summary, through the preparation method of the present application, the ultra-low temperature sintered composite ceramic material is successfully prepared at a temperature below 100° C., which can be applied to the packaging of silicon-based chips.
[0109] Compared with the prior art, the present application mainly has the following beneficial effects: the preparation method of the ultra-low temperature sintered ceramic material of the present application includes: preparing composite powder: placing a matrix formed by mixing ceramic raw materials and sintering aids in a ball mill, adding ball milling beads and ball milling media, mixing and ball milling, and then drying to form the composite powder; preparing pre-sintered material: adding deionized water to the composite powder after sieving, grinding in a mortar to form the pre-sintered material; preparing ultra-low temperature sintered ceramic material: adding the pre-sintered material to a mold, and performing ultra-low temperature sintering below 100°C to form the ultra-low temperature sintered ceramic material, and the ultra-low temperature sintering process includes two pressure holdings. The raw materials of the present application are easy to obtain, the process is simple, and by 3 BO 3 As a sintering aid, H 3 BO 3 The deformable property under uniaxial pressure allows the ceramic material to be densified under ultra-low temperature conditions of 25 to 100°C by applying pressure, and can be co-fired with silicon-based chips to form a composite ceramic material with good quality factor, suitable dielectric constant and excellent thermal conductivity, which can be well used in semiconductor packaging, LTCC devices or ULTCC devices, etc.
[0110] The embodiments described above are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention.
Claims
1. A method for preparing an ultra-low temperature sintered ceramic material, characterized in that: The following steps are involved: Preparation of composite powder: placing a matrix formed by mixing ceramic raw materials and sintering aids in a ball mill, adding ball milling beads and ball milling media, mixing, ball milling, and then drying to form the composite powder; Preparing the pre-sintered material: sieving the composite powder, adding deionized water, and grinding in a mortar to form the pre-sintered material; Preparation of ultra-low temperature sintered ceramic material: adding the pre-sintered material into a mold, and performing ultra-low temperature sintering below 100° C. to form the ultra-low temperature sintered ceramic material. The ultra-low temperature sintering process includes two pressure holdings, and the first pressure holding discharges air to improve the densification effect of the second pressure holding.
2. The method for preparing an ultra-low temperature sintered ceramic material according to claim 1, characterized in that: The ceramic raw material is at least one of Al2O3, AlN, and SiC; the sintering aid is H3BO3 powder; by weight, the ceramic raw material is 1 to 50 parts, and the H3BO3 powder is 1 to 50 parts.
3. The method for preparing an ultra-low temperature sintered ceramic material according to claim 2, characterized in that: The ceramic raw material is a flake particle with a diameter of 3 to 10 μm and a thickness of 0.1 to 1 μm.
4. The method for preparing an ultra-low temperature sintered ceramic material according to claim 3, characterized in that: The ball milling beads are zirconium balls, and the component is ZrO2; the ball milling medium is at least one of acetone, butanone, and hexanone.
5. The method for preparing an ultra-low temperature sintered ceramic material according to claim 1, characterized in that: The mass ratio of the substrate, the ball milling beads and the ball milling medium is 1:(2-4):
1.
6. The method for preparing an ultra-low temperature sintered ceramic material according to claim 1, characterized in that: The control conditions of the ball milling are: a rotation speed of 300-500 rpm and a time of 4-8 hours; the control conditions of the drying are: drying in a blower box and setting the temperature to 40-80° C. for a time of 12-36 hours.
7. The method for preparing an ultra-low temperature sintered ceramic material according to claim 1, characterized in that: The process of sieving the composite powder, adding deionized water, and grinding the composite powder in a mortar to form the pre-sintered material comprises the following steps: Sieve the composite powder through a sieve, wherein the mesh number of the sieve is 60 to 200 meshes; Deionized water is added to the composite powder, and the composite powder is ground in the mortar so that the deionized water wets the tiny particles of the composite powder.
8. The method for preparing an ultra-low temperature sintered ceramic material according to claim 7, characterized in that: The pre-sintered material is added into a mold and subjected to ultra-low temperature sintering below 100° C. to form the ultra-low temperature sintered ceramic material. The ultra-low temperature sintering process includes two pressure holding steps: Placing the pre-sintered material in a mold, performing the first pressure holding to expel air, setting the pressure to 100-200 MPa, the sintering temperature to 25-100° C., and the pressure holding time to 20-40 min; Then, the second holding pressure is performed to sinter and densify the pre-sintered material, the pressure is set to 100-800 MPa, the sintering temperature is set to 25-100° C., and the holding time is set to 40-150 min; Then, the mixture is dried at 65° C. to form the ultra-low temperature sintered ceramic material.
9. An ultra-low temperature sintered ceramic material, characterized in that: The ceramic material is prepared by the method for preparing an ultra-low temperature sintered ceramic material as described in any one of claims 1 to 8.
10. An application of ultra-low temperature sintered ceramic material, characterized in that: The ultra-low temperature sintered ceramic material according to claim 9 is applied to the packaging of silicon-based chips.
Citation Information
Patent Citations
Boron nitride ceramic material as well as preparation method and application thereof
CN116553935A
Microwave dielectric ceramic material, preparation method thereof and microwave communication device
CN117342870A
Production of low dielectric constant substrate
JP2000026163A
